POLLINATION STRATEGY CHOICE FOR ALFALFA - ARTOKHIN, KONSTANTIN S.; POLTAVSKY, ALEXANDER N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
The pollination strategy choice for alfalfa depends on two main factors: pollinator density in agro-ecosystems; and their faunal formation in the field. The natural occurrence of pollinators was estimated in southern Russia and sound to be of sufficient quantity to archieve complete alfalfa pollination. For solitary wild bee pollinator species was shown to establish highly mobile nomadic populations in agro-ecosystems.